The Effect of Strategic Supplier Partnership and Customer Relationship on Supply Chain Integration and Business Performance (Study of Red Onion Farmers in East Java) - Sumainah Fauziah; Kusdi Rahardjo; Hamidah Nayati Utami (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Abstract This research was conducted to determine the effect of strategic supplier partnership and customer relationship on farmer business performance through supply chain integration. This type of research is explanatory research with a quantitative approach. The data used in this study are primary data obtained by distributing questionnaires. The sampling method uses multistage proportional random sampling with a sample of 200 farmers. Data analysis in this study uses path analysis method with the help of SPSS 23. The results of this study indicate that strategic supplier partnerships have no significant effect on supply chain integration and farmer business performance. Customer relationship has a positive and significant effect on supply chain integration and farmer business performance, supply chain integration has a positive and significant effect on farmer business performance.